An all-inorganic lead-free halide perovskite Cs2InCl5(H2O) with heterogeneous oxygen for noncontact finger humidity detection. (15th April 2023) - Liu, Yi-Fei; Li, Cheng-Tao; Zhang, Le-Xi; Chong, Meng-Xiao; Bie, Li-Jian
Abstract: In this study, an all-inorganic lead-free halide perovskite Cs2 InCl5 (H2 O) was synthesized using a hydrothermal method. Considering the structural characteristics of Cs2 InCl5 (H2 O), this material is explored for room-temperature humidity-sensing application. We demonstrated that the Cs2 InCl5 (H2 O) sensor has excellent performance in the 11% to 97% relative humidity (RH) range, including high sensitivity (1.04 × 10 3 ), fast response (30 s), small hysteresis (0.38%), and good long-term stability (30 days). Consequently, this high performance enables the Cs2 InCl5 (H2 O) sensor to demonstrate great latent capacity in noncontact finger moisture detection. Finally, the humidity sensing mechanism was determined by using complex impedance spectra and corresponding equivalent circuits, demonstrating the role of charge carriers at different RH levels. This work provides a highly efficient sensing candidate for moisture detection, and more importantly offers a new strategy for the utilization of halide perovskites in high-performance sensory devices. Graphical abstract: An all-inorganic lead-free perovskite Cs2 InCl5 (H2 O) with heterogeneous oxygen was applied to humidity test for the first time with high performance, enabling great latent capacity in noncontact finger moisture detection. Image, graphical abstract